CBMT-02. miR-124, -128, AND -137 COMBINATION THERAPY AGAINST GLIOBLASTOMA. (5th November 2018) - Kosti, Adam; Qiao, Mei; Kokovay, Erzsebet; Penalva, Luiz
Abstract: miRNAs are critical regulators of tumorigenesis, acting as oncogenes or tumor suppressors. Previous work, by us and others, have demonstrated that miR-124, -128, and -137 are key players in controlling neurogenesis and gliomagenesis. Together these miRNAs promote differentiation of neural stem cells (NSCs), while in gliomas their dysregulation contribute to the glioma phenotype. The three miRNAs display strong expression correlation in GBM cohorts and synergize to drive neuronal differentiation of NSCs by regulating a shared network of genes. Individually ectopic overexpression of these miRNAs induces significant changes in proliferation, and differentiation of GBM cells; however, it is unclear if they synergize to produce a stronger effect as observed in NSCs. We tested the combination of miR-124, -128, and -137 in glioblastoma cell lines and found that together they produce a synergistic effect, decreasing cell proliferation and we will test this synergy in other systems. In NSCs we found an interconnected transcription factor (TF) network to be important targets of miR-124, -128, and -137. Due to their importance in NSCs, we hypothesized that these TFs are critical in gliomas. We performed a siRNA screen against the TFs network in GBM cell lines and examined the impact of knockdown on cell proliferation, viability, and apoptosis. While several genes were important in maintaining the glioma phenotype, knockdown of ETS-related transcription factor Elf-4 (ELF4) produced the strongest phenotype changes. We will next characterize ELF4's transcriptional influence utilizing ChIP-seq paired with RNA-seq. Overall our initial data suggests that this miRNA-Transcription factor network is important in the glioma phenotype, and that combination of the three miRNAs is synergistic. Furthermore, we find the ELF4 is a critical TF from this network and regulates the glioma phenotype.